A multi-product MPS optimization under risk - S. Al-Ashhab, M.; Fadag, Hassan; Mohammad Munshi, Shadi (International Journal of Engineering and Technology, 2019)
In this work, an MPS optimization model is developed to maximize the expected profit using GA under demand uncertainty. The model is built for @RiskOptimizer in MS Excel. The customer demands have been assumed to follow the normal distribution of a standard deviation related to their mean values with a ratio called demand variability. The effects of demand variability on the profit mean, profit variation and the processing time have been studied.Â